Prevalence of overweight and obesity among high school girls in Ardabil, Iran - Fattahzadeh-Ardalani, Ghasem; Masoumi, Rahim; Amani, Firouz; Zakeri, Anahita (International Journal of Advances in Medicine, 2017)
Background: Overweight and obesity and its problems are the most important health and nutrition issues of adolescents in developed countries. This study aimed to determine prevalence of overweight and obesity among high school girls in Ardabil. Methods: As a cross sectional study height, weight, waist circumference and hip circumference were measured. BMI and WHR were used to assess the overweight and obesity. Data analysed by statistical methods in SPSS.19. Results: The mean age of students was 16.6±1.1 years. 0.25 of students were in age 16. According to BMI, 8.8% of all students have overweight. According to the WHR, 72 (35.1%) had WHR >0.8 which were in unhealthy high risk group. Conclusions: Results showed that the rate of overweight and obesity in high school girls in Ardabil was lower than many studies in country. So, programming for rising their knowledge about obesity related factors and increasing their physical activity and modify feeding behaviour is essential.